1995
DOI: 10.1111/j.1365-2621.1995.tb09840.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds in Processed Duck Fillet

Abstract: Volatile components of smoked and dry-cured, smoked, brined or raw duck fillets were fractionated by simultaneous distillation-extraction before GUMS. Volatile compounds (62) identified were phenols, alcohols, ethers, aldehydes, ketones, hydrocarbons, acids, esters, terpenes and Nand S-compounds. Some compounds (34) were related to the smoke process. Most of these flavor compounds had been identified in smoked meat products and 7 are reported for the first time. The formation of aldehydes and alcohols mainly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
3
9
1
Order By: Relevance
“…However, most of them are long-chain aldehydes, acids, hydrocarbons, which can hardly be considered to strongly influence the flavour of NJMD. The result of SDE was consistent with the result of Wu & Liou (1992) and Lesimple et al (1995). Marta et al (2004) reported the similar result in dry-cured ham after the comparison of SPME and SDE.…”
Section: Comparison Of Three Extraction Techniquessupporting
confidence: 90%
See 2 more Smart Citations
“…However, most of them are long-chain aldehydes, acids, hydrocarbons, which can hardly be considered to strongly influence the flavour of NJMD. The result of SDE was consistent with the result of Wu & Liou (1992) and Lesimple et al (1995). Marta et al (2004) reported the similar result in dry-cured ham after the comparison of SPME and SDE.…”
Section: Comparison Of Three Extraction Techniquessupporting
confidence: 90%
“…Several S-and N-containing heterocyclic compounds were identified in NJMD (Table 1), which had been Wu & Liou (1992). § Compounds reported in Lesimple et al (1995).…”
Section: Flavour Compounds Of Nanjing Marinated Duckmentioning
confidence: 99%
See 1 more Smart Citation
“…[18,19] Similar results were obtained in the flavour research of raw duck meat, Nanjing marinated duck, Cantonese style roast duck and Nanjing water-boiled salted duck. [8,9,11,12] However, some highly volatile compounds (such as methanethiol) mentioned in the literature cited above were not identified in our study.…”
Section: Resultscontrasting
confidence: 48%
“…[6,7] However, few reports were on duck meat. To our best knowledge, Wu and Liou, [8] Lesimple and coworkers [9] and Ma et al [10] have analysed the volatile compounds of duck meat using traditional simultaneous distillationextraction (SDE) coupled with gas chromatography-mass spectrometry (GC-MS).…”
Section: Introductionmentioning
confidence: 99%